A measurement of the carbon sequestration potential of Guadua angustifolia in the Carrasco National Park, Bolivia - Ricardo A. Rojas Quiroga; Tracey Li; Gonzalo Lora; Lykke E. Andersen (Institute for Advanced Development Studies (INESAD), 2013)
The carbon sequestration potential of an unmanaged and previously unstudied Guadua angustifolia bamboo forest in the Carrasco National Park of Bolivia has been studied, by estimating the total aboveground biomass contained in the forest. It was found that the aboveground biomass consisting of stems, branches, and foliage, contains a total of 200 tons per hectare, leading to an estimated 100 tons of carbon being stored per hectare aboveground, which is comparable to some species of tree such as the Chinese Fir; this bamboo species therefore has the potential to play a significant role in the mitigation of climate change. The relation between the biomass, M, of each component (stems, branches, and foliage) and the diameter, d, of the plant was also studied, by fitting allometric equations of the form M = αdβ. It was found that all components fit this power law relation very well (R2 > 0.7), particularly the stems (R2 > 0.8) and branches (R2 > 0.9) for which the relation is found to be almost linear.
Keywords: Q23; Q54; 330; Climate change; mitigation; carbon sequestration; bamboo; Bolivia